Pyogenic granuloma of the glans penis after angioembolisation procedure - Yumnam, Deepak; Batra, Anmol; Paonam, Rikita; Dhiman, Avita (International Journal of Research in Medical Sciences, 2022)
Pyogenic granuloma (PG) of the glans penis in children is a rare entity. We herein report a young boy who develops PG after angioembolisation procedure.